OVERVIEW OF SLEEP QUALITY IN PERIPHERAL VERTIGO PATIENTS - Kiki Mohammad Iqbal & Mustafa Mahmud Amin (International Journal of Research Science and Management, 2019)
Background : Vertigo is the most common complaint in practice. There is a discussion about whether peripheral vertigo can affect sleep qualit. Objective: To determine the picture quality of sleep in patients with peripheral vertigo in Neurology and ENT Clinic in Haji Adam Malik Hospital and University of SumatraUtara Hospital. Method : This study is an analytic description with across sectional study approach . The sampling technique used is non-probability sampling, namely consecutive sampling. Data using primary data using questionnaires PSQI. Results: Of the 60 patients diagnosed with peripheral vertigo, BPPV obtained as many as 46 people (76.7%), Vestibular neuritis 7 (11.7%), Meniere's Disease 6 (10.0%), and labyrinthitis by 1 person (1.7%). In peripheral vertigo patients found poor sleep quality as many as 50 people (83.3%). Conclusion : It was found a picture of poor sleep quality significantly in peripheral vertigo patients.